Faktor-Faktor yang Mempengaruhi Kinerja Karyawan Perbankan: Studi pada PT. Bank Rakyat Indonesia (Persero) Cabang Batang - Hirarto, Arief Alfatah; Sartika, Mila (Department of Islamic Banking, Faculty of Islamic Economics and Business, Institut Agama Islam Negeri Pekalongan, 2021)
The purpose of this study is to describe and analyze the influence of leadership, intrinsic motivation, and career development on employee performance. The population in this study were 140 employees of PT Bank Rakyat Indonesia (Persero) Batang Branch. The sampling method used was purposive sampling method. Based on the data analysis, it can be concluded that there is a significant influence of the leadership variable on employee performance. There is a significant influence of the intrinsic motivation variable on employee performance. There is a significant influence of career development variables on employee performance. The variables of leadership, intrinsic motivation, and career development can affect employee performance by 41.8%.